1983
DOI: 10.3758/bf03197664
|View full text |Cite
|
Sign up to set email alerts
|

Duration judgment and the segmentation of experience

Abstract: Two experiments tested an interval segmentation explanation of duration judgment. In Experiment 1, a 170-sec time interval was filled with 27 unrelated words and three highpriority events (HPEs). These HPEs were clustered at the beginning of the interval (unsegmented condition) or distributed throughout the interval (segmented condition). Both recognition and recall of list information were measured, in addition to duration estimates. While no differences in memory performance were found, duration estimates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
86
0
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 9 publications
16
86
0
1
Order By: Relevance
“…However, Study 1 demonstrated that when the number of segments was augmented and repeated evenly, creating a routine, automatic feeling, the opposite occurred. Thus, whereas Poynter (1983) and Zakay et al (1994) found that the high-segmentation condition yielded longer time duration judgments than the low-segmentation condition in a nonroutine order of the segments, here the high-segmentation-routine condition yielded shorter time duration judgments than the highsegmentation-nonroutine condition and also the shortest time estimations of all the conditions. Hence, instead of the segments creating a change and becoming anchors to retrieve from memory, thus making duration seem longer, their automatic nature apparently created a unity that made time duration seem shorter.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, Study 1 demonstrated that when the number of segments was augmented and repeated evenly, creating a routine, automatic feeling, the opposite occurred. Thus, whereas Poynter (1983) and Zakay et al (1994) found that the high-segmentation condition yielded longer time duration judgments than the low-segmentation condition in a nonroutine order of the segments, here the high-segmentation-routine condition yielded shorter time duration judgments than the highsegmentation-nonroutine condition and also the shortest time estimations of all the conditions. Hence, instead of the segments creating a change and becoming anchors to retrieve from memory, thus making duration seem longer, their automatic nature apparently created a unity that made time duration seem shorter.…”
Section: Discussionmentioning
confidence: 95%
“…In past research on retrospective time estimations, a higher level of segmentation led to longer judgments of duration (Poynter, 1983;Poynter & Homa, 1983;Zakay & Feldman, 1993). Block (1978Block ( , 1989 related duration estimates with the number of changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first class assumes that duration is a by-product of non-temporal information processing; there is no specialized "timer" for measuring duration. For example, Ornstein (1969) argued that perceived duration depends upon the space needed to store the stimulus in memory, and others have stressed that time perception depends on the number of changes taking place during an interval (e.g., Block & Reed, 1978;Poynter, 1983). These storage-or change-based models have typically been applied to retrospective time judgments -where the participant does not know in advance that they will be asked for a time estimate -but they have also been related to the effects of stimulus motion on time perception in prospective tasks, where the observer knows that a time judgment will be required: More complex motion patterns are taken to lengthen apparent duration (Aubry, Guillaume, Mogicato, Bergeret, & Celsis, 2008) and faster speeds are taken to entail greater positional change and, accordingly, longer subjective time (S. W. Brown, 1995;Poynter, 1989).…”
Section: Time Winding Down: How Do Changes In Speed Affect the Percepmentioning
confidence: 99%
“…Severalof these variables (facets) are related to judgments on the duration of intervals (Galinat, 1984): (1) numberof stimuliperceivedduring a given interval (e.g., Buffardi, 1971;Frankenhauser, 1959;Mo, 1971;Ornstein, 1969); (2) amount of memory space required to store the events (e.g., Mulligan & Schiffman, 1979;Ornstein, 1969;Schiffman& Bobko, 1974, 1977; (3) difficulty (i.e., processing demands of the stimuli) DURAnON BELIEFS 309 (e.g., Avant, Lyman, & Antes, 1975;Burnside, 1971;Hicks et al, 1976;Michon, 1965;Thomas & Weaver, 1975;Vroon, 1970); (4) variability (i.e., the number of perceived changes of the stimuli) (Block & Reed, 1978;Fraisse, 1963;Poynter, 1983;Poynter & Homa, 1983); (5) evaluation (i.e., the perceived pleasantnessof stimuli (e.g., Edmonds, Cahoon, & Bridges, 1981;Harton, 1939;Langer, Wapner, & Werner, 1%1;Rosenzweig& Koht, 1933); (6) degree of anticipatory tension toward the occurrence of an event (e.g., Block, George, & Reed, 1980;Lordahl & Berkowitz, 1975); (7) attentional selectivity during encoding and retrieving of the stimuli (Underwood, 1975;Underwood & Swain, 1973) or attentional focusing on the passage oftime itself (e.g., Curton & Lordahl, 1974;Fraisse, 1963;McKay, 1977). Other researchers have presented somewhat different lists of facets.…”
mentioning
confidence: 99%